(untitled) (Research, Society and Development, 2022)
Oregano (Origanum vulgare L.) is a spice worldwide known and widely used as a seasoning in foods, in addition to being used in beverages and perfumeries. The dehydrated oregano extract is a substance rich in bioactive compounds, and stands out for its antioxidant and antimicrobial characteristics. The search for optimized processes, free of waste and not harmful to the environment has generated several researches, and the ultrasound technique is a promising technique that fits these requirements. In this study, an experimental design was developed to have optimal conditions for the extraction of phenolic compounds and antioxidants from dehydrated oregano, subtracting the ultrasound-assisted extraction, verifying the influence of the technique in the extraction of compounds. The independent variables were time (X1 = 2,5, 6,25 and 10 min), amplitude (X2= 20, 30 and 60%) and temperature (X3= 40, 50 and 60 °C). The ideal conditions obtained were time 10min, temperature 60ºC, amplitude 20%. The values obtained for phenolic compounds ranged from 17.17 to 345.14 mg of gallic acid equivalent (GAE) L-1 and for antioxidants from 509.37 to 1146.875 mmol of Trolox equivalent/g of extract.